The n-Generalized Schützenberger-crossed product of monoids - Çetinalp, Esra Kırmızı (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 512.5 We study the n-generalized Schützenberger-crossed product from the viewpoint of combinatorial group theory and define a new version of this product. For given monoids of this new product, we obtain a representation of the n-generalized Schützenberger-crossed product of arbitrary monoids.